2012
DOI: 10.1167/iovs.11-9134
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Stem Cells from Trabecular Meshwork Become Phagocytic TM Cells

Abstract: PURPOSE.To isolate and characterize stem cells from human trabecular meshwork (TM) and to investigate the potential of these stem cells to differentiate into TM cells. METHODS. Human trabecular meshwork stem cells (TMSCs) were isolated as side population cells by fluorescence-activated cell sorting or isolated by clonal cultures. Passaged TMSCs were compared with primary TM cells by immunostaining and quantitative RT-PCR. TMSC purity was assessed by flow cytometry and TMSC multipotency was examined by inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(149 citation statements)
references
References 32 publications
1
146
0
2
Order By: Relevance
“…To further confirm the identity of these cells as TM cells, we detected the expression of TM cell markers, including alphasmooth muscle actin (47,48), ADAMTS10 (49), CHI3L1 (50-52), and AQP1 (50,53,54). Our FACS, Western blot, and quantitative PCR (qPCR) analyses confirmed positive expression of all these markers in Cyp1b1 ϩ/ϩ and Cyp1b1 Ϫ/Ϫ TM cells (Fig.…”
Section: Disruption Of Collagen Fibers and Increased Oxidative Stressmentioning
confidence: 62%
“…To further confirm the identity of these cells as TM cells, we detected the expression of TM cell markers, including alphasmooth muscle actin (47,48), ADAMTS10 (49), CHI3L1 (50-52), and AQP1 (50,53,54). Our FACS, Western blot, and quantitative PCR (qPCR) analyses confirmed positive expression of all these markers in Cyp1b1 ϩ/ϩ and Cyp1b1 Ϫ/Ϫ TM cells (Fig.…”
Section: Disruption Of Collagen Fibers and Increased Oxidative Stressmentioning
confidence: 62%
“…Loss of TM cells has been suspected to contribute to aqueous humor outflow deficiencies and, conversely, it has been hypothesized that replacing lost cells can restore function to the eye (39). Previous studies by this and other laboratories have indicated that either multipotent cells isolated from the TM (40,41) or iPSC may be useful for this purpose (23,42). Indeed, recently published data have indicated that iPSC can restore some functional aspects in an organ culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Using SP cell sorting to purify stem cells was discovered in 1996 38 and has been used to isolate many kinds of adult stem cells. Since there are not enough cells from human TM tissue for direct SP cell sorting, we 39,40 first cultured and passaged cells from human TM in stem cell growth medium (SCGM) containing multipurpose reduced-serum media (Opti-MEM) supplemented with 5% fetal bovine serum (FBS), 10 ng/mL epidermal growth factor (EGF), 100 mg/mL bovine pituitary extract, 20 mg/mL ascorbic acid, 200 mg/mL calcium chloride, 0.08% chondroitin sulfate, 100 IU/mL penicillin, 100 mg/mL streptomycin, and 50 mg/mL gentamicin. After 2 to 3 passages, 5 · 10 5 -2 · 10 6 cells were incubated at 1 · 10 6 cells/mL in prewarmed DMEM with 2% FBS and either 5 mg/mL Hoechst 33342 41 or 10 mM DyeCycle Violet (DCV) 42 for 100 min at 37°C.…”
Section: Isolation and Cultivationmentioning
confidence: 99%